السلوك التمويلي للمؤسسات الاقتصادية الجزائرية في ظل سيادة التمويل غير المباشر - بوعريوة, الربيع; عدمان, فائزة (جامعة الوادي University of Eloued, 2020)
Despite the financialreformsapplied and the creation of a financialmarket in Algeria, the economyisstillclassifiedamong the economies of indebtednesssince the main exchange of the currencyisloans to the economy, because the mechanisms of the work of the financialpolicy of each country, and thenAlgeria, varyfrom country to country, according to whatischaracterized by itsinternalwealth, pitching money and the degree of development of itsfinancial system (the capital market), withoutforgetting the level of state intervention in economicactivity and its support for institutions this study aimed to shed light on the peculiarities of the Algerian financial system and its impact on the financing behavior of institutions in light of the secondary role of the financial market, and the study reached the rule of the indirect financing system through bank loans in the absence of an active financial market capable of supporting financing by borrowing Which necessitates activation
The Financing behaviour of Algerian economic institutions under indirect financing
مقال
Keywords: الكلمات المفتاحية: النظام المالي ،السوق المالي ،الجهاز المصرفي ،الحاجيات التمويلية،القروض.